(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Arinana A, Ardiansyah F, Andika R, Tarmadi D, Satimo. 2025. Identification of subterranean termites and their attack characteristics on settlements in Jakarta Province, Indonesia. Biodiversitas 26: 22-35. The increase in termite attacks on buildings in Jakarta, Indonesia coinciding with the city’s construction boom, is reshaping environmental dynamics. This study aims to identify the subterranean termite species responsible for damaging residential structures and to analyze the patterns of these infestations throughout Jakarta. The research was conducted across 57 settlement sites within the city, guided by a comprehensive survey of termite-induced damage and a four-month monitoring period from September to December 2021, during which Perseroan Terbatas (PT) Larusa Adi Sumindo, Jakarta implemented a baiting system. Morphometric identification of the termites revealed at least four species associated with building infestations: Coptotermes curvignathus, C. gestroi, Macrotermes gilvus, and Microtermes insperatus. Coptotermes gestroi was the most prevalent among these, found at 39 sites. The findings indicate that termite damage was most severe in window and door frames (49.1%), while the foundation exhibited the least damage (3.5%). This research highlights not only the diversity of termite species infesting urban areas but also the specific structural components vulnerable to their attacks, including frames, foundations, floors, walls, ceilings, archives, and garden trees. These insights are crucial for developing targeted mitigation strategies and building resilience against these pervasive subterranean termites, supporting sustainable urban development in Jakarta and beyond.